âGringsingâ Jalinan Estetika-Mitos Ritus Perang Pandan - Aryandari, Citra (Institut Seni Indonesia Yogyakarta, 2010)
Estetic and Mytos of Pandanus War. Gringsing The name of Gringsing is explained in popular etymology asmeaning free from sickness, which is in itself enough to indicate that the cloths are honoured by the people becauseof their magic infl uence. The origin of the gringsing cloths is traced back to Dewa Indra, who created shadowsin the sky so that they could be copied as pattern in the cloths. As was pointed out, the weaving of the gringsing,a sacred activity for the women. The weaving women have to take a number of adat regulations into account.Throughout Bali weavers are srict in following the adat. In he village of Tenganan Pegringsingan itself the use ofcertain gringsings is prescribed for specifi ed ceremonies. Tenganan Pegringsingan community perform religiousrites everyday to maintain the balance of the village. Tenganan Pegringsingan has unique culture, and all refer tothe concept of balance. The most famous ritual activities in Tenganan Pegringsingan is Pandanus War. In PandanusWar, gringsing always used by Truna and Daha. They believe in using gringsing, they will be spared from disease.Gringsing present in Tenganan Pegringsingan bringing myths and aesthetics. Gringsing is a picture of a communitycultural order Tenganan Pegringsingan. All have been recorded in awig-awig Tenganan Pegringsingan.